Development of an Integrated Inquiry Learning Model Using a Deep Learning Approach in Elementary School - Mustikasari, Lindy; Sumartiningsih, Sri; Sumarni, Woro (Universitas Muhammadiyah Surakarta, 2026)
This research was motivated by the urgency of improving the quality of education and learning outcomes for elementary school students to ensure they are relevant to 21st-century competencies. The primary objective of this study was to validate the Inquiry Learning (IL) development model combined with the Deep Learning (DL) approach and to test its effectiveness on students' cognitive learning outcomes. The method used was Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) framework, involving fifth-grade students in five elementary schools as research subjects. Data were collected through expert validation instruments, observations, and learning outcome tests (pre-test and post-test), which were then analyzed using N-Gain inferential statistics. The results showed that the IL-DL model was deemed highly valid and practical by experts and practitioners. Key findings revealed a significant improvement in cognitive learning outcomes; in a small-scale trial, the completion rate jumped dramatically from 30% in the pre-test to 95% in the post-test. This consistent effectiveness was reinforced by a large-scale trial, with a completion rate of 94.6%. Furthermore, the average N-Gain Score (g) of 0.78 (High category) and the effectiveness level of 78.54% (Effective category) confirm that the synergy between structured inquiry and in-depth learning successfully mitigates the phenomenon of shallow learning. This study concludes that the IL-DL model is a transformative solution worthy of adoption to improve the quality of learning and student competencies in elementary schools.